PEMANFAATAN DAN PELAPORAN ANJAK PIUTANG (FACTORING) - Emita Wahyu Astami (UGM, 2000)
Factoring is the purchases of a firm's accounts receivables (the client) by another firm (the factor) for a discount fee. This paper attempts to discuss the benefit of factoring receivables, steps taken to avoid serious problems that can arise from factoring, and reporting the sales of receivables.